2013
DOI: 10.3892/or.2013.2257
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single-, double- and triple-combined testing, including Pap test, HPV DNA test and cervicography, as screening methods for the detection of uterine cervical cancer

Abstract: Abstract. Cervical cancer is a serious disease that threatens the health of women worldwide. This study compared the sensitivities and false-positive rates of cervical cytology (Pap smear), human papilloma virus (HPV) DNA test, cervicography, first double-combined testing (cervical cytology and HPV DNA test), second double-combined testing (cervical cytology and cervicography) and triple-combined testing (cervical cytology, HPV DNA test and cervicography). The study included 261 patients screened for uterine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Pap smears, although a gold standard in the prevention of cervical cancer, has insufficient sensitivity. The high rate of false negative results of cervical cytology leads to the misdiagnosis of many cervical cancer patients [5]. Currently, an additional HPV (Human Papilloma Virus) - genotyping screening program has been introduced to improve the diagnostic sensitivity [68].…”
Section: Introductionmentioning
confidence: 99%
“…Pap smears, although a gold standard in the prevention of cervical cancer, has insufficient sensitivity. The high rate of false negative results of cervical cytology leads to the misdiagnosis of many cervical cancer patients [5]. Currently, an additional HPV (Human Papilloma Virus) - genotyping screening program has been introduced to improve the diagnostic sensitivity [68].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although the Pap smear is inexpensive, it is less accurate than the HPV-DNA test; therefore, screening at wider intervals with the highlysensitive HPV-DNA test may be more cost-effective than the current system (Gravitt et al, 2010;Levin et al, 2010;Chen et al, 2011;Flores et al, 2011;Shi et al, 2011). While HPV-DNA tests are not covered under the current NCSP, previous studies comparing screening methods have reported that the sensitivity of the Pap smear was improved markedly in combination with the HPV-DNA test (Kim et al, 2013). Further research examining the cost-effectiveness of single and combination test screening should be conducted to determine the most practical cancer screening strategy.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] Cervicography The practice of cervicography involves obtaining a photographic image of the cervix which were coincidently or later read by certified experts, as an adjunct to the Papanicolaou smear. 49 This highlights the fact that as we increase sensitivity through a multimodal approach, specificity may suffer. In a comparison of cervicography to conventional cytology by Kesic and colleagues, the sensitivity and specificity were calculated by assessing an asymptomatic population in a University Clinical Center Belgrade.…”
Section: Visual Screeningmentioning
confidence: 99%